The Effect of Quintuple Helix in Increasing Creativity and Innovation to Competitive Advantage the Creative Village in Bandung Municipality West Jawa Province - Heru Dwi Wahana; Muh Ilham; Kusworo Kusworo; Mansyur Mansyur; Dedeh Maryani (Budapest International Research and Critics University, 2022)
The creative economy has contributed to economic development, but the development of the creative economy still has many problems, especially human resources, so that it has an impact on weak competitive advantage and performance. The purpose of this study was to examine the effect of the quintuple helix in increasing creativity and innovation and its impact on the competitive advantage of creative villages in the Bandung City Government, Java Bandung. The research method is mixed methods, namely quantitative and qualitative. The quantitative approach uses the statistical method of the Partial Least Square-Structural Equation Modeling (PLS-SEM) structural equation model, while the qualitative method uses descriptive and Soft System Methodology (SSM). For the quantitative approach, the sampling used Cluster Random Sampling with multi-stage cluster sampling and the data analysis used Partial Least Square- Structural Equation Modeling (PLS-SEM). The results showed that the quintuple helix (intellectuals, government, business, civil society, social ecology) had a significant effect on creativity and innovation. While the dimensions of the quintuple helix variables, namely intellectuals, government, civil society, social ecology have a significant effect on creativity, but business has no significant effect on creativity. Intellectuals, government, and civil society have a significant effect on innovation, but business and social ecology have no significant effect on innovation. Creativity has a significant effect on innovation. Creativity and innovation capability have a significant effect on the competitive advantage of creative villages. Meanwhile, for the descriptive approach and SSM produce a sextuple helix model which is a development of the quintuple helix model by adding a media helix and Information and Communication Technology (ICT) and in managing creative villages, metagovernance management is needed.